A igreja e a família: âncoras na travessia do meio - Machado, Ana Cláudia Oliveira (2009)
This present research got as a goal to punctuate the changes suffered by the institutions: Church and Family, "anchors" and significant contributions to adolescence (through the middle). Accosting the church and the role from the teenagers family, members from the Baptist Church in Valença - BA, in the presence of physical changes, emotional, mental and spiritual from ones children and how these changes can contribute to the psychosocial development and teenagers maturation to help them in forming the construction of their identity and survive in a world in constant changes.